EVALUATION AND RATIONING OF NATURAL LOSS OF OIL PRODUCTS IN FLEXIBLE TANKS - Y. N. Ribakov (Научный вестник МГТУ ГА)
An effective technique for experimental studies to determine the losses of petroleum products in flexible tanks is suggested. Standards of technological losses of petroleum products on the permeability, swelling and wetting flexible tanks are defined.